2023
DOI: 10.1109/access.2023.3247967
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Image Dehazing Using Heterogeneous Atmospheric Light Prior

Abstract: Remote sensing images (RSIs) captured in haze weather will suffer from serious quality degradation with color distortion and contrast reduction, which creates numerous challenges for the utilization of RSIs. To address these issues, this paper proposes a novel haze removal algorithm, named HALP, for visible RSIs based on a heterogeneous atmospheric light prior and side window filter. HALP is comprised of two key components. Firstly, given the large imaging space of RSIs, the atmospheric light is treated as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…It is imperative to acknowledge that the diminished intensity observed in the dark channel primarily stems from shadows cast by the scene, the presence of dark objects, and vividly colored surfaces or objects. The dark channel a priori defogging algorithm, grounded in statistical principles, has demonstrated commendable outcomes within the realm of image defogging, exhibiting greater stability in comparison to the aforementioned non-physical model algorithms [34][35][36][37][38]. This algorithm can more accurately estimate the thickness of the fog, resulting in a more natural and clearer defogging effect [39][40][41].…”
Section: Dark Channel Prior (Dcp)mentioning
confidence: 99%
“…It is imperative to acknowledge that the diminished intensity observed in the dark channel primarily stems from shadows cast by the scene, the presence of dark objects, and vividly colored surfaces or objects. The dark channel a priori defogging algorithm, grounded in statistical principles, has demonstrated commendable outcomes within the realm of image defogging, exhibiting greater stability in comparison to the aforementioned non-physical model algorithms [34][35][36][37][38]. This algorithm can more accurately estimate the thickness of the fog, resulting in a more natural and clearer defogging effect [39][40][41].…”
Section: Dark Channel Prior (Dcp)mentioning
confidence: 99%
“…For the purpose of dehazing aerial images, Kulkarni et al [24] suggested a novel deformable multi-head attention mechanism with a spatial attention offset extraction solution. For visible light Remote Sensing Imagery (RSI), He et al [25] presented a unique haze removal algorithm known as HALP based on heterogeneous atmospheric light prior and side window filtering. An algorithm for dehazing visible light remote sensing images, called SRD, was presented by He et al [26].…”
Section: Image Dehazementioning
confidence: 99%
“…To validate the dehazing ability of the SRD algorithm on remote sensing images, we compare and analyze the haze removal results of SRD and other state-of-the-art methods on real-world haze images. All test samples are from the Real-world Remote Sensing Haze Image Dataset (RRSHID) [44], which contains 277 degraded images with haze, all of which are manually selected by the authors of RRSHID from two widely used remote sensing datasets, AID [45] and DIOR [46]. In this experiment, we employ three types of test samples for a more comprehensive assessment: (1) challenging samples with dense haze; (2) images with different color distributions; and (3) remote sensing haze images of various scenes.…”
Section: Qualitative Experiments On Real-world Remote Sensing Image D...mentioning
confidence: 99%
“…Here, we comprehensively compare the average processing time of various dehazing algorithms for input images with different resolutions. We randomly select 100 images from the RRSHID dataset [44] mentioned in Section 4.2 and resize them to three resolutions: 256 × 256, 512 × 512, and 1024 × 1024, constituting three test sets. Then, we execute the SRD algorithm and each comparison method separately on the same computer (described in Section 4.1) and calculate their average computing time on these three test sets.…”
Section: Execution Efficiencymentioning
confidence: 99%